Rotigotine transdermal patch in Chinese patients with early Parkinson's disease: A randomized, double-blind, placebo-controlled pivotal study. (July 2016) - Zhang, Zhen-Xin; Shang, Hui-Fang; Hu, Xingyue; Chen, Shengdi; Zhao, Zhongxin; Du, Xinlu; Surmann, Erwin; Bauer, Lars; Asgharnejad, Mahnaz
Abstract: Introduction: Two phase3 studies (SP512; SP513) involving mostly Caucasian patients showed that rotigotine (≤8 mg/24 h) was efficacious and welltolerated in early-stage Parkinson's disease (PD). We report results from a phase 3 study (SP0914/NCT01646268) investigating rotigotine in Chinese patients with early-stage PD. Methods: Patients were randomized 1:1 to rotigotine or placebo, titrated over 1–4 weeks, maintained at optimal/maximum dose (≤8 mg/24 h) for 24 weeks. Primary efficacy variable: change in Unified Parkinson's Disease Rating Scale (UPDRS) II + III total score from Baseline to End-of-Maintenance. Secondary variables: UPDRS II + III responders (≥20% decrease in UPDRS II + III) and changes in UPDRS II (activities of daily living [ADL]) and III (motor examination) subscores. Results: Of 247 patients randomized, 113/124 (91.1%) rotigotine- and 107/123 (87.0%) placebo-treated patients completed the study. Patients: mean (SD) age: 59.4 (10.2) years; time since PD diagnosis: 1.01 (1.22) years, 60.7% male. Rotigotine significantly improved UPDRS II + III total score (change from Baseline LSmean [95%CI] treatment difference, −4.82 [−7.18 to −2.45]; P < 0.0001). UPDRS II + III responder rates were higher with rotigotine (42.3% vs 22.3%; P = 0.0006). UPDRS II and III subscores improved with rotigotine (both subscores: P < 0.0005 vs. placebo). Most frequent adverse events (AEs): nausea (8.9% rotigotine, 3.3% placebo), dizziness (8.1%, 5.7%), pruritus (8.1%, 4.1%), somnolence (8.1%, 3.3%), erythema (6.5%, 1.6%), and vomiting (5.6%, 1.6%). Thirteen (5.3%) patients discontinued due to AEs (6 rotigotine, 7 placebo). Conclusions: Rotigotine was efficacious in Chinese patients with early-stage PD, providing benefits to control of ADL and motor function. Rotigotine was generally welltolerated, with similar AEs to those observed in Caucasian patients. Highlights: This is the first study of rotigotine in Chinese patients with early-stage PD. Rotigotine significantly improved the UPDRS II + III total score vs placebo. Rotigotine improved UPDRS II + III responder rates and II/III subscores vs placebo. Rotigotine was generally well tolerated, with no new safety signals. Efficacy/safety profiles of rotigotine were similar to those in Caucasian patients.